2023
DOI: 10.1186/s12933-023-01879-4
|View full text |Cite
|
Sign up to set email alerts
|

Tofogliflozin long-term effects on atherosclerosis progression and major clinical parameters in patients with type 2 diabetes mellitus lacking a history of cardiovascular disease: a 2-year extension study of the UTOPIA trial

Abstract: Background This study aimed to assess the long-term effects of tofogliflozin, a sodium-glucose cotransporter 2 (SGLT2) inhibitor, on atherosclerosis progression and major clinical parameters in patients with type 2 diabetes lacking an apparent history of cardiovascular disease. Methods This was a prospective observational 2-year extension study of the “Using TOfogliflozin for Possible better Intervention against Atherosclerosis for type 2 diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…SGLT2 inhibition has been shown to improve arterial stiffness. A meta-analysis comparing the PWV between the SGLT2 inhibitors-dapagliflozin and empagliflozin-versus placebo found that SGLT2 inhibitors reduced PWV by 0.76 m/s [40], while an observational study with tofogliflozin showed a worsening of arterial stiffness in non-tofogliflozin but not in patients on tofogliflozin [41]. Further details of the impact of SGLT2 inhibitors on vascular function measurements are presented in Supplementary Table S1.…”
Section: Effects Of Sglt2 Inhibitors On Vascular Functionmentioning
confidence: 99%
“…SGLT2 inhibition has been shown to improve arterial stiffness. A meta-analysis comparing the PWV between the SGLT2 inhibitors-dapagliflozin and empagliflozin-versus placebo found that SGLT2 inhibitors reduced PWV by 0.76 m/s [40], while an observational study with tofogliflozin showed a worsening of arterial stiffness in non-tofogliflozin but not in patients on tofogliflozin [41]. Further details of the impact of SGLT2 inhibitors on vascular function measurements are presented in Supplementary Table S1.…”
Section: Effects Of Sglt2 Inhibitors On Vascular Functionmentioning
confidence: 99%